Kebijakan Mutasi dan Kepuasan Pegawai dalam Kerangka Organization-Employee Relationship (OER) - Mhd. Ricky Karunia Lubis; Veren Yolanda; Lola Inganta Saragih; Kuat Sidik Wahyono; Nauval Muhammad; Mentari Hanan Salsabila (Scientax: Jurnal Kajian Ilmiah Perpajakan Indonesia, 2025)
Employee dissatisfaction with transfer policies has a negative impact on the organization, not only because it affects employee performance but also because it forces employees to decide to leave the organization. A decline in performance and employee resignations become serious issues amid the continuously increasing tax revenue targets and the organization's inability to increase the number of employees in a short time. The issue becomes even more complicated when the employees who resign are the organization's best talents. Therefore, it is crucial for the Directorate General of Taxes (DJP) to design transfer policies that can provide satisfaction for employees. Transfer policies may not always meet employee desires. However, transfer policies can at least be designed to ensure certainty and equal treatment for all employees. The primary data sources for this study were obtained through an online survey, which employs a quantitative methodology. This study uses the Organization-Employee Relationship (OER) framework to examine the factors that influence employee satisfaction with the transfer policy within DJP using Partial Least Square-Structural Equation Model (PLS-SEM) analysis. Specifically, the objective of this investigation is to assess the impact of exchange relationship and communal relationship on employee satisfaction with the transfer policy within DJP, as mediated by three OER qualities: trust, commitment and control mutuality. The research reveals that employee satisfaction with the organization is significantly and positively influenced by employee satisfaction with the transfer policy. The satisfaction with the transfer policy is only influenced by the transactional relationship between employees and DJP when it is mediated by trust and control mutuality. Conversely, employee satisfaction with the transfer policy is directly influenced by communal relationships. This relationship is later strengthened by trust and control mutuality.